Pemberdayaan Perempuan Melalui Pelatihan Pengolahan Ikan Lele dan Diversifikasi Produk di UMKM Mutiara Timur - Ihwan Ridwan; Dian Wahyudi (Universitas Muhammadiyah Parepare)
The women's empowerment program is the most important sector that must be considered in national development. Great women must have expertise at least in politics, economics, religion, law, and education so as not to become subordinates in the life of the state. Strengthening the status of women's position is contained in the Universal Declaration of Human Rights, an effort made in improving the standard of living of society by providing knowledge and skills to create empowered women. Through the women's empowerment program which is carried out together with UMKM Mutiara Timur partners, this is a form of concern about gender equality. Some of the problems faced by partners are as follows: 1) the product produced is only grated; 2) raw materials that are not available at any time due to lack of information obtained about catfish cultivator producers; 3) marketing systems that still rely on distributors and message production; and 4) non-standard product packaging. Efforts made in advancing the business carried out with four approaches, namely (1) providing training in the diversification of catfish preparation; (2) providing training and assistance to collaborate with farmers in Makassar and surrounding areas; 3) provide marketing management training and provide access to modern markets so that their products are known; and 4) provide product packaging training. Transforming the knowledge and skills provided to couples can increase family economic income. The results of the implementation of activities in the form of mentoring cooperation with marketing partners, business licenses, and suppliers (breeders) of catfish around Makassar.